Assessing catalytic converter degradation in emission reduction: comparative study of co, THC, and NOx across mileage, engine capacity, and transmission type - Hasan Basri; Akhmad Andriyan Nugroho; Ayu Pratiwi; Jong, So Rhee; Farrah Anis Fazliatul Adnan; Dianta Ginting (Universiti Malaysia Sabah, 2025)
Environmental concerns have led to stricter global emission standards for combustion engine vehicles. This study evaluates the degradation patterns of catalytic converters in reducing CO, THC, and NOx emissions across 20 passenger vehicles with varying mileage (up to 100,000 km), engine capacities (1.2 - 1.5L), and transmission types (manual/automatic). Four catalytic converter designs (Types A-D) were assessed using the New European Driving Cycle (NEDC) methodology for compliance with Indonesian and EURO-4 standards. Results revealed that Type D converters maintained the best performance for CO (0.2 - 0.4 g/km) and THC emissions (0.02 - 0.04 g/km) with stable degradation across their lifespan. Conversely, Type B exhibited significant degradation (degradation factor 9.0) and higher emission levels overall. Statistical analysis showed significant differences in THC emissions between converter types (p < 0.05), while differences in CO and NOx were not statistically significant (p > 0.05). NOx emissions showed the highest degradation factor (5.78) across all converter types. This research demonstrates the critical relationship between catalytic converter design, vehicle operational parameters, and emission reduction effectiveness over time, providing insights for future catalyst material development and maintenance strategies to maintain long-term environmental compliance.